(untitled) (Universal International Scientific Journal, 2026)
The younger school age is considered a period of rapid development of cognitive processes, and at the same time, with the help of modern digital technologies, there is an opportunity to achieve a consistent improvement in the function of nerve centers, and as a result, to increase the learning performance of students. Below, the impact of digital systems on the cognitive characteristics of students of the younger school age is analyzed from a neuropsychological perspective.